Confidence Intervals in Official Statistics: The Case of Lithuania - Čiginas, Andrius (Lithuanian Journal of Statistics, 2012)
In the paper, the application of confidence intervals in the surveys of official statistics is discussed. It is noticedthat there are situations where at the first sight natural normal distribution-based confidence intervals are not suitable. Wedemonstrate it by examples taken from Lithuanian statistical surveys. We also discuss an Edgeworth expansion and abootstrap method as an alternative to the normal approximation.
Keywords: confidence interval; normal approximation; Edgeworth expansion; bootstrap; finite population